1991
DOI: 10.1007/bf01543008
|View full text |Cite
|
Sign up to set email alerts
|

Transsexual healing: Medicaid funding of sex reassignment surgery

Abstract: Federal requirements for state Medicaid programs are surveyed, and case law regarding Medicaid funding of sex reassignment surgery is reviewed. States have attempted to exclude sex reassignment surgery (SRS) from Medicaid coverage on various bases, concluding, for example, that the procedure constituted "cosmetic surgery." Judicial scrutiny of such exclusions has usually resulted in the state action being found violative of the federal Medicaid statute and accompanying regulations. In those cases upholding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Thus, it is difficult to determine the effectiveness of hormones alone in the relief of gender dysphoria. A comprehensive review of over 2,000 patients in 79 studies by Pfäfflin andJunge between 1961 and1991 reported favorable effects of sex-reversal therapies including hormones and surgery based mainly on observational findings (Pfäfflin & Junge, 1998). Most patients seeking sex-reversal therapy report improved psychosocial outcomes ranging between 87% (MtF) and 97% (FtM) (Green & Fleming, 1990).…”
Section: Effectiveness Of Hormone Therapymentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, it is difficult to determine the effectiveness of hormones alone in the relief of gender dysphoria. A comprehensive review of over 2,000 patients in 79 studies by Pfäfflin andJunge between 1961 and1991 reported favorable effects of sex-reversal therapies including hormones and surgery based mainly on observational findings (Pfäfflin & Junge, 1998). Most patients seeking sex-reversal therapy report improved psychosocial outcomes ranging between 87% (MtF) and 97% (FtM) (Green & Fleming, 1990).…”
Section: Effectiveness Of Hormone Therapymentioning
confidence: 98%
“…In addition, the current SOC does not provide discussion of the medical 146 Jamie Feldman and Joshua Safer 147 necessity or data on the effectiveness of crossgender hormone therapy. The absence of this critical information conveys a sense of crossgender hormone therapy as either experimental or cosmetic in nature, discouraging providers, health care systems, and insurers from approaching it as part of standard medicine (Gordon, 1991;Thaler, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, transgender patients are among the most socially stigmatized of sexual minorities, facing discrimination in health care coverage and insensitivity from ill-informed health providers (Bockting et al, 1998;Clements, Wilkinson, Kitano, & Marx, 1999;Gordon, 1991;Kammerer, Mason, Connors, & Durkee, 1999;Lombardi, 2001;Lombardi & van Servellen, 2000). Transgender-specific health care rarely is a covered benefit.…”
mentioning
confidence: 97%
“…Similar situations have been found in other studies, 27---29 reflecting the problems that these patients have in order to obtain hormone treatments in public hospitals in and out of Spain, consequently increasing the risk of complications. 30 Despite the fact that there are no similar studies in Mexico, we should take the data into account given the risks that self-medication involves.…”
Section: Treatmentmentioning
confidence: 99%